Reflecting on healthcare and self-care in the Intensive Care Unit: our story - Allan Peterkin; Andrew Baker; Ronna Bloom; Nikki Marks (University of Bologna, 2014)
Health care professionals working in Intensive Care Units (ICUs) are exposed to high levels of stress-provoking stimuli. Some may unconsciously employ negative coping skill s which may contribute to burnout and negatively affect patient care. We chose to explore ways of facilitating and encouraging self-reflective practice in an effort to increase empathic traits and enhance communication. A narrative medicine series, which included six sessions that were focused on different narrative approaches, was organized for staff of an academic teaching hospital. Totally, 132 interdisciplinary ICU staff attended the sessions. They were generally open to exploring the selected approaches and discussing their reflections within the interdisciplinary environment. The narrative medicine series provided tools for health care professionals to enhance self-reflective skills utilizing a team-based learning approach. The anticipated outcomes were improved self-care, increased empathy and communication skills, enhanced team functioning, which all contribute to better patient care at the bedside.